Pelatihan Pembuatan POC dari Sampah Organik Rumah Tangga di Kelompok PKK RW 27 Tegal Boto Lor Jember - Rudi Wardana; Liliek Dwi Soelaksini; Sepdian Luri Asmono; Ilham Muhklisin; Tirto Wahyu Widodo; Ana Uzunul Mauidah; Niko Atha Ramadhan (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The waste problem is a major issue that has not been optimally resolved. RW 27, Tegal Boto Lor Environment, Sumbersari Village, Sumbersari Subdistrict, Jember Regency, also faces the same problem in waste management. The purpose of this activity is to reduce the amount of household organic waste and increase family income by selling Liquid Organic Fertilizer (POC). This community service is conducted by providing training on POC production and business management of the resulting products so that partners can later produce organic fertilizer from organic waste on a commercial scale. The results of this community service include partners gaining an understanding of POC, from its advantages to the processing of organic waste into POC. The survey results show an 80% increase in knowledge among the partners. In the production of POC, one of the materials used is EM-4, which functions as a starter to accelerate the decomposition process. The POC production process takes 1 to 4 weeks, characterized by a white surface and an aroma similar to tape. The next step is the packaging process in 1-liter containers